Encyclopedia of Industrial Biotechnology 2009
DOI: 10.1002/9780470054581.eib065
|View full text |Cite
|
Sign up to set email alerts
|

Basidiomycetous Yeasts for Production of Carotenoids

Abstract: While Saccharomyces cerevisiae is the most widely exploited yeast in biotechnology, it cannot be forgotten that this species represents only a small percentage of blastomycetes biodiversity. Currently, in fact, numerous other species are being utilized or studied for potentially important roles such as many basidiomycetous yeasts. Nevertheless, in spite of their enormous biosynthetic potential, studies regarding their many useful catalytic attributes and products are still primarily con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 149 publications
0
1
0
Order By: Relevance
“…However, the Antarctic marine ecosystem remains largely unexplored and few studies have investigated the yeasts that inhabit the Antarctic seas. To date, yeasts from the genera Candida, Cryptococcus, Cystofilobasidium, Guehomyces, Leucosporidium, Metschnikowia, Mrakia, Rhodosporidium, Rhodotorula, Sympodiomyces, Sakaguchia and Sporopachydermia have been isolated from seawater, marine sediments, invertebrate organisms and algae, among other Antarctic marine environments (Nagahama, 2006;Kutty & Philip, 2008;Shivaji & Prasad, 2009;Loque et al, 2010;Hua et al, 2010;Song et al, 2010;Buzzini et al, 2012;Vaca et al, 2013). The importance of the study of Antarctic marine yeasts has been pointed by genus-wise distribution studies, which showed that marine yeasts from Antarctic oceans have the least similarity compared with the yeast biodiversity from the other oceans (Kutty & Philip, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Antarctic marine ecosystem remains largely unexplored and few studies have investigated the yeasts that inhabit the Antarctic seas. To date, yeasts from the genera Candida, Cryptococcus, Cystofilobasidium, Guehomyces, Leucosporidium, Metschnikowia, Mrakia, Rhodosporidium, Rhodotorula, Sympodiomyces, Sakaguchia and Sporopachydermia have been isolated from seawater, marine sediments, invertebrate organisms and algae, among other Antarctic marine environments (Nagahama, 2006;Kutty & Philip, 2008;Shivaji & Prasad, 2009;Loque et al, 2010;Hua et al, 2010;Song et al, 2010;Buzzini et al, 2012;Vaca et al, 2013). The importance of the study of Antarctic marine yeasts has been pointed by genus-wise distribution studies, which showed that marine yeasts from Antarctic oceans have the least similarity compared with the yeast biodiversity from the other oceans (Kutty & Philip, 2008).…”
Section: Introductionmentioning
confidence: 99%